2022
DOI: 10.1021/acsami.1c19565
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Substrates with Molecular-Level Perfluoroalkyl/Alkylamide Surface for Laser Desorption/Ionization Mass Spectrometry of Small Proteins

Abstract: The rapid detection of biomolecules greatly contributes to health management, clinical diagnosis, and prevention of diseases. Mass spectrometry (MS) is effective for detecting and analyzing various molecules at high throughput. However, there are problems with the MS analysis of biological samples, including complicated separation operations and essential pretreatments. In this study, a nanostructured organosilica substrate for laser desorption/ionization mass spectrometry (LDI-MS) is designed and synthesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 56 publications
(91 reference statements)
0
15
0
Order By: Relevance
“…In contrast to those conventional substrates, silica serves as an ideal candidate for LDI chip substrate due to the low thermal conductivity (7.6 W m/ (m•k)), high chemical stability, low background interference, and adjustable pore structure (Zhao et al, 2022). Very recently, Norihiro et al reported nanoporous organosilica membranes with a pore size of ~150 nm as a novel substrate for small protein detection in LDI-MS (Mizoshita et al, 2022). While to achieve a direct and sensitive detection of small metabolites (<5 nm) in bio-fluids, the mesoporous silica substrate needs to be carefully designed to couple with the LDI-MS chip for high sensitivity and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to those conventional substrates, silica serves as an ideal candidate for LDI chip substrate due to the low thermal conductivity (7.6 W m/ (m•k)), high chemical stability, low background interference, and adjustable pore structure (Zhao et al, 2022). Very recently, Norihiro et al reported nanoporous organosilica membranes with a pore size of ~150 nm as a novel substrate for small protein detection in LDI-MS (Mizoshita et al, 2022). While to achieve a direct and sensitive detection of small metabolites (<5 nm) in bio-fluids, the mesoporous silica substrate needs to be carefully designed to couple with the LDI-MS chip for high sensitivity and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…25 We further extended the tailor-made surface design to detect a trace amount of an amyloid β-protein fragment, which is an important biomarker for Alzheimer's disease. 26 In a prior study, an alkylamide group was introduced into the naphthalimide moiety and a perfluoroalkyl group reacted with silanol, leading to a mixed surface, where opposite functional groups were distributed at the molecular level. The mixed surface achieved the detection of 0.2 fmol μL −1 of amyloid β in the presence of blood-related components.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Matrix-free LDI-MS has been developed using UV-absorbing solid substrates, such as nanostructured silicon, metal oxide nanoparticles, and carbon materials, where the absorbed laser energy is transferred to analyte molecules for desorption and ionization. Recently, we proposed the use of organosilica films as promising solid substrates. The matrix-free LDI technique, which is especially useful for analyzing low-molecular-weight compounds, including drugs, peptides, lipids, and agrochemicals, would be helpful for rapid screening of trace SU herbicide residues in environmental and food analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the process of radiotherapy in patients was monitored, and a preliminary panel of metabolites in serum was identified [20]. Mizoshita et al designed nanoporous substrates with molecular-level perfluoroalkyl/alkylamide surface for LDI-MS of small proteins [21]. Surface functionality was tuned by mixing perfluoroalkyl/alkylamide groups at a molecular level, and the amyloid fragment, which was suggested as a biomarker of Alzheimer's disease, was detected at a concentration of 0.2 fmol/µL in the presence of other blood compounds [21].…”
Section: Introductionmentioning
confidence: 99%
“…Mizoshita et al designed nanoporous substrates with molecular-level perfluoroalkyl/alkylamide surface for LDI-MS of small proteins [21]. Surface functionality was tuned by mixing perfluoroalkyl/alkylamide groups at a molecular level, and the amyloid fragment, which was suggested as a biomarker of Alzheimer's disease, was detected at a concentration of 0.2 fmol/µL in the presence of other blood compounds [21]. Palladium nanoparticle-decorated thiol-functionalized metal-organic framework (MOF) nanocomposite was fabricated for the sensitive analysis of oligosaccharides [22].…”
Section: Introductionmentioning
confidence: 99%